Indicators of enterprise activity quality - Ковалев, А. И.; Зенкин, А. С. (Problems of Informatization and Control, 2014)
The article considers assessing enterprise activity quality as performing work, as well as in the context of requirements and recommendations of management process standards, that is, basing on productivity, efficiency and achieving lasting success. Justification of hierarchic assessment scheme is provided, as well as that of identification of the three value groups, and the empirical rule of the value choice ‘10/80/10’ – through its presentation by hyperbolic distribution. This rule has to be considered as an additional condition of balance of balanced sets of values, along with isolating activity aspects